2012
DOI: 10.3109/13625187.2012.694147
|View full text |Cite
|
Sign up to set email alerts
|

‘Female condoms give women greater control’: A qualitative assessment of the experiences of commercial sex workers in Swaziland

Abstract: Although female condom use involves negotiation with clients, the fact that it offers sex workers an independent method of protection gives them more power and also, increases their ability to control their sexual and reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 24 publications
0
69
0
Order By: Relevance
“…As a result of these gendered power imbalances, one group of scholars has advocated for the replacement of the concept of safe sex (i.e., sexual activity that's protected from unintended pregnancy and/or STIs) with woman-controlled safe sex (Alexander, Coleman, Deatrick, & Jemmott, HIGGINS AND SMITH 2012). Along those lines, the call for women-controlled dual-prevention technologies, such as female condoms and microbicides, consistently highlights the notion that women need access to methods that they can use covertly, regardless of their male partners' knowledge or participation (Mathenjwa & Maharaj, 2012). Though woman-controlled safe sex is a powerful and necessary feminist concept, it may be less relevant to those situations in which women's heterosexual activity is consensual and, ideally, mutually pleasurable.…”
Section: Part 1: Building a Conceptual Model Of Sexual Acceptability mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these gendered power imbalances, one group of scholars has advocated for the replacement of the concept of safe sex (i.e., sexual activity that's protected from unintended pregnancy and/or STIs) with woman-controlled safe sex (Alexander, Coleman, Deatrick, & Jemmott, HIGGINS AND SMITH 2012). Along those lines, the call for women-controlled dual-prevention technologies, such as female condoms and microbicides, consistently highlights the notion that women need access to methods that they can use covertly, regardless of their male partners' knowledge or participation (Mathenjwa & Maharaj, 2012). Though woman-controlled safe sex is a powerful and necessary feminist concept, it may be less relevant to those situations in which women's heterosexual activity is consensual and, ideally, mutually pleasurable.…”
Section: Part 1: Building a Conceptual Model Of Sexual Acceptability mentioning
confidence: 99%
“…Even though contraceptives are used within sexual and relational interactions, contraceptive acceptability research largely has been remiss in assessing partnership factors. In some ways, this omission has been purposeful: Research on womencontrolled technologies has deliberately tried to provide women with contraceptives they could use independently of their partners' knowledge or participation (Mathenjwa & Maharaj, 2012;Naidu, 2013). In other ways, this omission has come with a cost, particularly in terms of fully understanding the sexual aspects of contraceptives.…”
Section: Relationship Factors: Dyadic Influences and Partner Preferencesmentioning
confidence: 99%
“…In the majority of studies on female condoms, only women have been interviewed (see Beksinska, Smit, Joanis, & Hart, 2012; Feldblum et al, 2000; Joanis et al, 2011; Kulcyzki, Kim, Duerr, Jamieson, & Macaluso, 2004; Mathenjwa & Maharaj, 2012; Napierala, Kang, Chipato, Padian, & van der Straten, 2008; Sly, Quadagno, Harrison, & Eberstein, 1997; Weeks, Coman, Hilario, Li, & Abbot, 2013; Zachariah et al, 2003). As a result, much of what is known about men’s perceptions and experiences of the device is based solely on women’s accounts of their experiences with male partners.…”
Section: Men and Female Condomsmentioning
confidence: 99%
“…The 2009 Modes of Transmission Study reports that heterosexual transmission accounts for the majority of HIV infections in Swaziland and sex work is a minor driver of the epidemic; however, it also acknowledges that little information is known about this hidden population [36]. A literature review revealed only two peer-reviewed studies conducted on sex workers in Swaziland [37], [38]. Although sex work is not criminalized in Swaziland, activities related to sex work, such as the solicitation and procurement of sex in public, are illegal [39], which makes conducting research among this population difficult yet essential to understanding factors shaping their HIV-related risk.…”
Section: Introductionmentioning
confidence: 99%